2020
DOI: 10.34172/ehem.2020.02
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of heavy metals contamination and ecological risk between soils enriched with compost and chemical fertilizers in the North of Iran and ecological risk assessment

Abstract: Background: Nowadays, uncontrolled use of chemical fertilizers in agriculture is one of the reasons for the entry of heavy metals into the environment. In this study, the heavy metals contamination of the soils enriched with compost and chemical fertilizers in the North of Iran and its ecological risk assessment were evaluated. Methods: In this study, 108 soil samples were collected from agricultural soils of some places of Babol in Mazandaran province. An atomic absorption spectrophotometer (PG-990) was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…This study showed that BTEX was significantly reduced during the mixed sludge vermicomposting process. Therefore, in general, the results of this study are consistent with the results of other similar studies (33)(34)(35)(36)(37)(38)(39)(40). However, the results of this study have some differences with those of some previous studies according to the method of work, bed characteristics, sludge type, treatment method, test conditions, study time, number and characteristics of earthworms and bed microorganisms.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This study showed that BTEX was significantly reduced during the mixed sludge vermicomposting process. Therefore, in general, the results of this study are consistent with the results of other similar studies (33)(34)(35)(36)(37)(38)(39)(40). However, the results of this study have some differences with those of some previous studies according to the method of work, bed characteristics, sludge type, treatment method, test conditions, study time, number and characteristics of earthworms and bed microorganisms.…”
Section: Discussionsupporting
confidence: 88%
“…Hosseini Panah and Takdastan concluded that the ratio of 2:1 mixing of oil-based drilling mounds with sludge biological vermicomposting has the highest TPHs decomposition efficiency compared to other percentages of waste mixing over a period of 60 days in this study (34). Amouei et al also reported that hazardous compounds such as heavy metals were significantly reduced by the composting process on soil in the North of Iran (35). Opuada Ameh et al also investigated the effect of earthworms (Eudrilus eugeniae) on the removal of organic Benzene (mg/kg) compounds in engine oil.…”
Section: Discussionmentioning
confidence: 99%
“…Cd is an environmental pollutant heavy metal that enter the environment by both natural and synthetic sources (16)(17)(18). The most important sources of artificial soil contamination include discharge of sludge and industrial wastewater, the use of fertilizers and superphosphate, buried non-ferrous scrap in the ground and agricultural lands around mines of Pb and zinc or refineries (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, phosphate compounds in the contaminated soils such as Pb pollution are known as a suitable method for stabilization of heavy metals (16)(17)(18). However, the efficiency of such compounds in soils with physical and chemical properties is not similar (19), which needs to be studied separately in different studies.…”
Section: Introductionmentioning
confidence: 99%